Optimalisasi Sistem Informasi Manajemen Pendidikan Dalam Peningkatan Mutu Pengelolaan Lembaga Pendidikan Islam (Studi Deskriptif Kualitatif di SD Muhammadiyah Ponorogo) - Elsa Defita Sari; Fahrisha Zuhrotul Mardliyah; Frezha Dwi Kurnia Putri; Roni Harsoyo (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah dan Ilmu Keguruan, IAIN Ponorogo, 2023)
Every educational institution basically requires an information system to maximize the implementation of the information cycle at the institution. In addition, to control quality and create relationships with other parties to optimize the quality of these educational institutions, This research was conducted to review more deeply the Education Management Information System (SIMDIK) in Muhammadiyah Ponorogo Elementary School (SD) with a research focus to describe the application of SIMDIK in improving the quality of management at SD Muhammadiyah Ponorogo. The type of research used is qualitative research with a descriptive approach. Data collection techniques using interviews, observation, and documentation The data analysis technique used Miles and Huberman's interactive model. The results of this study indicate that the application of SIMDIK in improving the quality of SD Muhammadiyah Ponorogo management includes: 1) institutional information systems, personnel, infrastructure, student affairs, finance, and academics have been running optimally; 2) the e-learning system and library information system run optimally by taking into account the intended use; 3) SIMDIK, which has been running optimally, can improve the quality of management at Muhammadiyah Ponorogo Elementary School and provide benefits for internal and external parties.